2019
DOI: 10.1097/prs.0000000000005264
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Botulinum Toxin Type A in the Healing of Thyroidectomy Wounds: A Randomized, Prospective, Placebo-Controlled Study

Abstract: Background: Recent research has indicated that botulinum toxin type A may have an inhibitory effect on the formation of fibroblasts and thus possibly decreases the severity of scar formation. Therefore, a trial was designed to assess the effects of botulinum toxin type A on scar formation after thyroid surgery. Methods: A double-blind, randomized, controlled trial was designed. All patients underwent a preoperative survey to assess scar history. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 22 publications
3
42
0
Order By: Relevance
“…According to the authors, this may be because this scale is applicable to the evaluation of burn scars, but not highly sensitive to nonburn scars. In the study of Phillips et al, there were no obvious difference in VSS, OSAS, and PSAS between the two groups; but the subgroup analysis found that BTXA in patients with a history of severe scars has a certain effect. The authors believe that it may be influenced by the origin of the wound and its relationship with tension lines, and speculate that the higher proportion of patients with a history of severe scars in other studies may lead to the inconsistent results .…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…According to the authors, this may be because this scale is applicable to the evaluation of burn scars, but not highly sensitive to nonburn scars. In the study of Phillips et al, there were no obvious difference in VSS, OSAS, and PSAS between the two groups; but the subgroup analysis found that BTXA in patients with a history of severe scars has a certain effect. The authors believe that it may be influenced by the origin of the wound and its relationship with tension lines, and speculate that the higher proportion of patients with a history of severe scars in other studies may lead to the inconsistent results .…”
Section: Discussionmentioning
confidence: 87%
“…In the study of Phillips et al, there were no obvious difference in VSS, OSAS, and PSAS between the two groups; but the subgroup analysis found that BTXA in patients with a history of severe scars has a certain effect. The authors believe that it may be influenced by the origin of the wound and its relationship with tension lines, and speculate that the higher proportion of patients with a history of severe scars in other studies may lead to the inconsistent results . However, no relevant analysis has been carried out in other included studies, and the number of cases in this study is small, with a large number of people lost to follow‐up.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations